Hong Kong’s Currency and Monetary Policy - Richard Fast (Financial Markets, Institutions and Risks, 2021)
This literature review is a synopsis of what has been written on the currency and monetary policy of Hong Kong since its relinquishment from Great Britain in 1999. In particular, this paper examines the role and policies of the Hong Kong Monetary Authority, the island province’s equivalent to a central bank. Since Hong Kong does not have a central bank per se, it is interesting to note how the money supply is created and maintained, and what its relationship is to mainland China. This institution makes Hong Kong unique among developed economies, which typically have a central bank that oversees monetary creation and policy. The Literature Review is composed of two parts: Part One will cover the revaluation of the Hong Kong Dollar with regard to its value relative to the currencies of China, Japan, Europe, and the United States, particularly during financial crises. This part of the literature review will cover the work of Chan (2002), Schenk (2004), Shah (1996), Cook and Yetman (2004), and Ma and Cheng (2014) as they use different measurement methods to monitor the change in the Hong Kong Dollar’s value over time, especially compared to the period before the creation of the Hong Kong Dollar. Part Two will cover the monetary and macro-economic policies and currency board effectiveness of the Hong Kong Monetary Authority in sustaining the value of the Hong Kong Dollar. This part of the literature review will cover the work of Chen (2001), Siregar and Walker (2000), Chen and Tsang (2020), Funke and Paetz (2000), and Huang and Shen (2017). This paper also includes a section on suggestions for future research, including what effect the shift of pegging the Hong Kong Dollar (HKD) to other currencies, such as the Euro or the Japanese Yen, or when interest rates in other countries are set at zero. The paper wraps up with an overview of the literature discussed and possible paths going forward, including recreating the studies over time to see how effective such a maneuver has been in practice when compared to competing currencies. Followers of the Hong Kong Dollar will especially find these results useful as they seek to exchange currencies for the highest value.